Proceedings of the 2nd Workshop on New Frontiers in Summarization 2019
DOI: 10.18653/v1/d19-5405
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Aspect-Based Multi-Document Abstractive Summarization

Abstract: User-generated reviews of products or services provide valuable information to customers. However, it is often impossible to read each of the potentially thousands of reviews: it would therefore save valuable time to provide short summaries of their contents. We address opinion summarization, a multi-document summarization task, with an unsupervised abstractive summarization neural system. Our system is based on (i) a language model that is meant to encode reviews to a vector space, and to generate fluent sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…Product review summarization is a form of multi-document summarization in which a set of product reviews for a single product serves as the document cluster to be summarized. A common approach for product review summarization, which centers the summary around a set of extracted aspects and their respective sentiment, is termed aspect-based summarization (Hu and Liu, 2004;Kansal and Toshniwal, 2014;Wu et al, 2016;Angelidis and Lapata, 2018;Coavoux et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…Product review summarization is a form of multi-document summarization in which a set of product reviews for a single product serves as the document cluster to be summarized. A common approach for product review summarization, which centers the summary around a set of extracted aspects and their respective sentiment, is termed aspect-based summarization (Hu and Liu, 2004;Kansal and Toshniwal, 2014;Wu et al, 2016;Angelidis and Lapata, 2018;Coavoux et al, 2019).…”
Section: Related Workmentioning
confidence: 99%
“…These baselines were selected because the previous evaluation task concludes that the term clustering is the more promising and effective setting for topic modeling in our proposal. Thus, it allows us to evaluate the performance of the different approaches of our model and to compare them with notable summarizers as TextRank [41] (a similar decision is adopted in References [46,47]).…”
Section: Resultsmentioning
confidence: 99%
“…However, averaging representations of statements that are sometimes contradictory tends to confuse the decoder, and might lead it to ignore the input signal. To deal with this limitation, Coavoux et al (2019) add a clustering step to group similar reviews and to generate one sentence per such found cluster. Bražinskas et al (2020) proposed to solve the problem of unsupervised opinion summarization with an auto-encoder with latent variables.…”
Section: Related Workmentioning
confidence: 99%